KANDUNGAN LOGAM BERAT PADA BIJI KAKAO ASAL SULAWESI BARAT DAN TENGGARA - Ristanti, Eky Yenita; Suprapti, Suprapti; Ramlah, Sitti (Jurnal Industri Hasil Perkebunan, 2016)
Research on heavy metals content in cocoa beans from West and Southeast Sulawesi hasbeen done. This research aims to identify heavy metals content, which are Pb, Cu, Cd and Zn in cocoa beansfrom West and Southeast Sulawesi. Results shows that Pb content in cocoa beans from West Sulawesi is inthe interval of 49,616 ppm (Mamuju) â 112,343 ppm (North Mamuju); Cu 141,362 ppm (Mamuju) â 198,04ppm (North Mamuju); Cd 0,0494 ppm (Mamasa) â 0,7468 (Polman); Zn 193,186 ppm (Polman) â 247,362ppm (North Mamuju). Pb content of cocoa beans from Southeast Sulawesi is in the interval of 33,783 ppm(Kendari) â 112,912 ppm (North Kolaka); Cu 119,162 ppm (Muna) â 180,728 ppm (Kolaka); Cd 0,0769 ppm(Bombana) â 0,6676 (North Kolaka) dan Zn 29,21 ppm (Bombana) â 214,12 ppm (North Kolaka).Keywords: heavy metals, cocoa beans, SNI 7387:2009, West Sulawesi, Southeast Sulawesi